Issues in Web-based pedagogy : a critical primer - Cole, Robert A., 1958- (Greenwood educators' reference collection., 2000)
Annotation The essays in this collection consider the theoretical and practical concerns of online teaching and learning. Aiming at an interdisciplinary audience, the contributors draw upon their diverse theoretical and empirical backgrounds to highlight issues associated with this increasingly popular educational technology.